(untitled) (Research, Society and Development, 2020)
Fungal cocultures can promote complex interactions that result in physiological and biochemical alterations that favor the synergic and more efficient action of extracellular enzymes such as laccase. Thus, coculture can be used as a strategy to increase enzymatic activity, dye degradation, and bioremediation of textile effluents. This study aimed to evaluate the coculture effect of Lentinus crinitus, Pleurotus ostreatus, Pycnoporus sanguineus, and Trametes polyzona on laccase activity, mycelial biomass production, and in vitro decolorization of azo, anthraquinone, and triphenylmethane dyes. The species were cultivated in liquid medium in monoculture and coculture in paired combinations for 15 days to determine the laccase activity and produced mycelial biomass. The enzymatic extracts of fungal cultivations were used in decolorization tests of reactive blue 220 (RB220), malachite green (MG), and remazol brilliant blue R (RBBR). Pleurotus-Trametes, Lentinus-Pleurotus, and Lentinus-Trametes cocultures increase laccase activity compared to respective monocultures. Lentinus-Pycnoporus, Lentinus-Trametes, Lentinus-Pleurotus, and Pleurotus-Trametes cocultures stimulate mycelial biomass production in relation to their respective monocultures. The enzymatic extracts of monocultures and cocultures promoted the decolorization of all dyes. RB220 dye presented fast decolorization. In 24 h, all extracts reached maximum decolorization and the greatest color reduction percentage was 90% for Pleurotus-Trametes coculture extract. Pleurotus-Trametes extract also increased the decolorization of MG and RBBR dyes when compared to their respective monocultures in 48 h and 72 h, respectively. However, RBBR dye presented the greatest resistance to decolorization.